The organizational period in the Jordanian employment contract - Al-Harazneh, Kutibah Hamid; Al-Maaitah, Mohammad Fawwaz; Al-Maaitah, Othman Fathi (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to demonstrate the importance of the organizational periods and the domain of applying them in the Jordanian employment law, especially that the law didn't address the concept of organizational period and didn't show the periods that are considered within organizational periods within the Jordanian employment law. The study used the analytical descriptive approach, where the study investigated the legal laws and the courts' rules relevant to the study topic.The organizational period in the Jordanian employment contract refers to the period mentioned by the Jordanian legislator and forced individuals to apply it according to certain rules. The researchers addressed the organizational period in the Jordanian employment contract by dividing the study into two topics, where the first topic addressed the extent to which the periods of individual work contract are considered as valid from the organizational periods. The study demonstrated the meaning of limited-time individual employment contract and the non limited-time employment contract and then demonstrated the difference between them. In the second topic, the researchers discussed the period of judging the urgent cases and illustrated the extent to which they are considered within the organizational periods.  The researchers concluded with a number of results and recommendations, including that the non limited-time contracts imply that the party intending to terminate the contract should inform the other party within a period of one month at least, and the Jordanian employment law stated that the magistrate Court should adjudicate the employment disputes within no more than three months. The study recommended the necessity of urging the Jordanian legislator to amend the Jordanian employment law No. 8 of 1996 by determining the time period during which the limited-time employment contract is valid in order to consider it within the organizational period, since the Jordanian legislator stated in the Jordanian civil law No. 43 of 1976. The study also recommended that the Jordanian legislator should determine a certain period of time for litigation before the authority of rents and organize that in a legal way to ensure implementing it in the right way.
Keywords: regulatory period; work contract; labor law; Jordan